Quality Of Lithuanian Classical Fiction Ebooks User’s Approach - Grigas, Vincas; Petraitytė, Simona; Akstinaitė-Veličkienė, Eglė (Knygotyra, 2014)
Digital book publishing is developed in accordance with proven methodologies, the quality of digital books keeps getting better and is aligned to the needs of digital generation readers. All kinds of libraries are gradually getting involved in digital book publishing, but this kind of activity is still new and posing a variety of challenges. The aim of this article is to establish the activity of National libraries in EU member states in creating digital fiction and leisure books on the basis of their cultural heritage collections, and to evaluate the quality of these books from the user‘s perspective. The objectives are to investigate how many National libraries of EU member states are creating digital fiction books on the basis of their cultural heritage collections; to evaluate the quality of these digital books according to A. Gudinavičius (2012) quality criteria for digital books (navigation, technical aspects, information organization, privacy and security settings, etc.); to compare the quality of the books from different EU member states‘ National libraries and to measure the quality in 3 different devices: digital book reader, touchpad and personal computer.All 28 National libraries were questioned if they are creating digital books on the basis of their cultural heritage collections. Only Lithuanian, Hungarian and French National libraries create and provide free access to digital books in EPUB format. Six digital books (2 from each National library) were chosen for investigation.It was found that all 6 books meet the minimum quality requirements. Some sets of criteria, such as the pleasure to read, visual appearance, are rated not as good as navigation, privacy and security settings. Given the fact that these books are published for leisure reading, developers of digital books should pay more attention to visual solutions, so the book quality could be higher.Among the 3 EU member states (Lithuania, Hungary and France) French digital books have the highest quality. The visual appearance of these books almost equal commercial publishers‘ digital books. Meanwhile Lithuanian and Hungarian digital books lack the visual perfection, attention to details, which have a major impact on satisfaction and willingness to continue reading the book.It was found that the most proper device for reading digital books is Apple iPad, because it provides maximum functionality and aesthetics. Less functional is Nook digital book reader, although it also renders the book well enough. Reading books using personal computer is least comfortable, because Adobe Digital Editions 2.0 software provides the user with extremely limited functionality options.In summary it can be stated that the first steps taken by libraries in creating digital books in EPUB format are successful. If the weaknesses emphasized in this study were removed, the users could get a high-quality final product which would be attractive for members of digital generation.
Keywords: ...